Représentations des risques d’inondation, adaptation et évacuation en Île-de-France - Samuel Rufat; Emeline Comby; Victor Santoni; Odile Plattard; Serge Lhomme; Eric Enderlin (Cybergeo, 2025)
The study of risk perception determinants and their impacts on the levels of preparedness of exposed populations often leads to inconclusive results across case studies. Numerous competing theories and hypotheses have been formulated across different disciplines, but their empirical validation remains a challenge. The current fragmentation of research on risk perception hampers the cross-validation of previous results, which might make the field appear as a collection of independent case studies in some instances. We use a flood risk perception and emergency behaviour survey in Paris, France(n=2976), to discuss a theoretical and methodological approach to consolidating the position of geography in the field, better disentangling social and spatial factors. The research questions are structured around the role of hazard exposure, prior experience, place of residence, and social vulnerability on risk perception and emergency behaviour. The main hypothesis is that previous inconclusive results published in the literature on risk perception determinants stem from divergent disciplinary approaches and theories, as well as from the at times uncertain place of geography in the field.